A Blot on the Landscape? Civic memory and municipal public parks in early twentieth-century Manchester. (3rd July 2017) - O'Reilly, Carole
ABSTRACT: This paper examines the decision to locate the façade of Manchester's old Town Hall in a public park (Heaton Park) in 1912. It argues that, in so doing, the city's Parks and Cemeteries committee was attempting to refine the didactic space of the park as a site of civic memory. The early Victorian urban parks had sought to educate their visitors through their museums, art galleries and exhibition spaces, glasshouses and carefully planned and planted walkways. The insertion into this environment of part of a former civic building was intended to remind the visitors of their civic history and to warn surrounding districts of the expansionist tendencies of the city of Manchester. The failure to identify the façade or to connect it to its surroundings meant that its meaning was ultimately lost to many parks visitors and it remained in place as a civic folly. Public parks presented the municipal authorities with an opportunity to highlight the provision of recreation and leisure facilities, but also an occasion to re-invent the municipal tradition. However, as this paper shows, such gestures were often futile in the complex and contested space of the public park.